Influence of Vapour Smoothing Process Parameters on Fused Deposition Modelling Parts Surface Roughness at Different Build Orientation. (2020) - John Rajan, A.; Sugavaneswaran, M.; Prashanthi, B.; Deshmukh, Siddhant; Jose, S.
Abstract: Additive Manufacturing is becoming increasingly important to the manufacturing industry with the gradual rise in the complexity of products and technology. In this paper, influence of finishing method i.e vapour smoothing process parameters on fused deposition modelling surface finish is studied. Process parameters considered for investigation in this study are build orientation, volume of chemical solution used for finishing and vapour smoothing process time. The test specimen is fabricated in polylactic acid thermoplastic using CubePro FDM machine and THF (Tetra Hydro Flouride) solution is used for vapour smoothing. From experimentation, it is observed that finishing method has significant influence and among the process parameters notable impact is observed in build orientation. Minimum surface roughness is observed at 90°orientation, 10ml volume of THF and VS process time of 5 minutes. Work presented in this study will further enhance the application of FDM parts in patterns for casting, and consumer goods which required high surface finish